Moderasi Beragama dan Kohesi Sosial di Perguruan Tinggi: Kerangka Strategis untuk Mengembangkan Sikap Sosio-Religius pada Mahasiswa - Mo'tasim, Mo'tasim; Alfiatin, Yuliana (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2024)
The rise of intolerance and fanaticism that has occurred recently, especially in public universities, demands the importance of implementing religious moderation as a solution in creating a peaceful and violence-free religious life. Religious moderation is a strategic approach to deal with the rise of radicalism and intolerance among university students, who are vulnerable to the influence of extreme ideologies. This study aims to explore the implementation of religious moderation in building a harmonious learning atmosphere at Institut Teknologi Adi Tama Surabaya (ITATS), a campus with students from diverse religious and cultural backgrounds. Using a qualitative approach with a case study design, data were collected through in-depth interviews, participatory observation, and documentation. The results showed that religious moderation at ITATS centers on the application of the concept of tawassuth (the middle way), which is integrated into the curriculum and other campus activities. The program is effective in improving tolerance and socio-religious attitudes, minimizing potential conflicts, and strengthening social cohesion among students. The findings confirm the importance of religious moderation education as a strategy to strengthen national awareness and develop inclusiveness in a multicultural academic environment